2021
DOI: 10.1002/dad2.12179
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarker panel for synaptic dysfunction in Alzheimer's disease

Abstract: Introduction Synaptic dysfunction and degeneration is one of the earliest events in Alzheimer's disease (AD) and the best correlate of cognitive decline. Thus, identification and validation of biomarkers reflecting synaptic degeneration to be used as prognostic biomarkers are greatly needed. Method Solid‐phase extraction and parallel reaction monitoring mass spectrometry were used to quantify 17 synaptic proteins in CSF, in two cross‐sectional studies including AD (n = 52) and controls (n = 37). Results Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 45 publications
11
82
2
Order By: Relevance
“…Consequently, the reduction of NPTX2 could be linked to the disruption of pyramidal neuron-PV interneuron microcircuit, contributing to cognitive failure in AD (Xiao et al 2017). This was further sustained by studies that found NPTX2 correlating with medial temporal atrophy, hippocampal volume and cognitive impairment (Nilsson et al 2021;Swanson et al 2016;Xiao et al 2017). In addition, new evidence suggested NPTX2 as a strong prognostic biomarker candidate of cognitive decline (Libiger et al 2021).…”
Section: Alzheimer's Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, the reduction of NPTX2 could be linked to the disruption of pyramidal neuron-PV interneuron microcircuit, contributing to cognitive failure in AD (Xiao et al 2017). This was further sustained by studies that found NPTX2 correlating with medial temporal atrophy, hippocampal volume and cognitive impairment (Nilsson et al 2021;Swanson et al 2016;Xiao et al 2017). In addition, new evidence suggested NPTX2 as a strong prognostic biomarker candidate of cognitive decline (Libiger et al 2021).…”
Section: Alzheimer's Diseasementioning
confidence: 94%
“…NPTXs seemed to moderately correlate with many synaptic markers (e.g., β-synuclein, γ-synuclein, neurogranin, syntaxin, SNAP25) in the healthy control and the AD group. Intriguingly, they declined in AD patients, opposite to the other synaptic markers that primarily increased in CSF (Galasko et al 2019;Nilsson et al 2021). As for non-AD conditions, NPTX2 correlated with CSF levels of other synaptic proteins such as neurosecretory protein VGF and α-synuclein in DLB (Boiten et al 2020).…”
Section: Correlation Between Nptxs and Other Recognised Markers Of Neurodegenerationmentioning
confidence: 99%
“…The copyright holder for this this version posted August 24, 2021. ; https://doi.org/10.1101/2021.08.17.21262131 doi: medRxiv preprint 8 disease 16,17 . Thus, we measured these three markers in CSF from the KaSP cohort (FEP patients n=43; HCs n=19).…”
Section: Figure 1)mentioning
confidence: 99%
“…Lastly, as C4A CNs predict synaptic complement deposition and synaptic pruning in experimental models 6 , we explored associations between CSF C4A protein concentrations and an in vivo proxy of synapse density. CSF levels of neuronal pentraxins (1, 2, and receptor) were recently shown to inversely correlate with prefrontal cortical thickness determined with MRI, as well as to predict synapse loss in dementia and Alzheimer's 8 disease 16,17 . Thus, we measured these three markers in CSF from the KaSP cohort (FEP patients n=43; HCs n=19).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation